Computer Study of a Thermocouple with Developed Lateral Heat Transfer - Cherkez, R.G.; Porubanyi, O.M.; Konstantynovych, I.A.; Tomko, S.O. (Journal of Thermoelectricity, 2025)
The work is devoted to the study of thermoelectric generator elements with developed lateral heat exchange, which allows increasing their efficiency. Using the Comsol Multiphysics software environment, a three-dimensional model of a thermoelement with developed lateral heat exchange was created. The influence of the leg height and the velocity on the efficiency, the power generated by the thermoelement, the voltage and other characteristics was studied.